Vloge orodjarn v dobavni verigi - Fulder, Tatjana (Strojniški vestnik, 2001)
This paper deals with the importance of involving suppliers in new-product development and focuses on the toolmaking industry because of its integration into the supply chain. Using a case-study methodology an in-depth analysis of the situation in the Slovenian toolmaking sector was carried out in order to identify the roles of toomakers in the supply chain and in new-product development in relation to their capabilities. The results of the research are summarized in a model of the roles of toolmakers in the supply chain, in which the roles reflect the different stages of development of individual capabilities.
Keywords: orodjarstvo; razvoj izdelkov; dobavitelji; verige dobaviteljev; orodje; dobava